2015
DOI: 10.1371/journal.pone.0131353
|View full text |Cite
|
Sign up to set email alerts
|

Trends in AIDS Deaths, New Infections and ART Coverage in the Top 30 Countries with the Highest AIDS Mortality Burden; 1990–2013

Abstract: BackgroundAntiretroviral therapy (ART) prevents human immunodeficiency virus (HIV) disease progression, mortality and transmission. We assess the impact of expanded HIV treatment for the prevention of Acquired Immunodeficiency Syndrome (AIDS)-related deaths and simulate four treatment scenarios for Nigeria and South Africa.MethodsFor 1990–2013, we used the Joint United Nations Programme on HIV/AIDS (UNAIDS) database to examine trends in AIDS deaths, HIV incidence and prevalence, ART coverage, annual AIDS death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(133 citation statements)
references
References 27 publications
4
128
0
1
Order By: Relevance
“…In the era of antiretroviral therapy (ART), there have been striking decreases in acquired immune deficiency syndrome (AIDS)‐related mortality 1, 2, 3 and prolongation of life expectancy 4, 5, 6, 7 for people living with HIV infection (PLWH). With this, there has been a shift in distribution of causes of death toward non‐AIDS‐defining events (NADEs) 8, 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…In the era of antiretroviral therapy (ART), there have been striking decreases in acquired immune deficiency syndrome (AIDS)‐related mortality 1, 2, 3 and prolongation of life expectancy 4, 5, 6, 7 for people living with HIV infection (PLWH). With this, there has been a shift in distribution of causes of death toward non‐AIDS‐defining events (NADEs) 8, 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Citation information for the data sources used for relative risks are provided in searchable form through a web tool. We estimate the joint eff ects of combinations of risk factors using the same methods as GBD 2013, namely using published studies to estimate the fraction of a risk that was mediated through the other risk (methods appendix pp [28][29][30][31][32][33][34][35]. Relative risks by age and sex for each risk factor and outcome pair are provided in the methods appendix (pp 215-44).…”
Section: ·2% 36·9%mentioning
confidence: 99%
“…Gains in SDI are likely to operate through many pathways, including improved access to health care, public health programmes, and social and welfare policy. Advances in treatment are well documented for various causes, including HIV/AIDS, [30][31][32] ischaemic heart disease, [33][34][35][36][37] and various cancers, [38][39][40] including breast, [41][42][43] testicular, 44 and Hodgkin's, 45 yet for other causes, such as oesophageal cancer and interpersonal violence, the policies, programmes, and interventions responsible for declining risk-deleted death and DALY rates are less clear than for the aforementioned causes. Improvement of understanding of the risk-deleted rates in cause-specifi c mortality and disease burden will strengthen the evidence base for intervention eff ectiveness, the role of …”
Section: Rethinking the Risk Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, it was found that the causative agent of AIDS was HIV. Currently, over 35 million individuals are HIV infected worldwide with the highest prevalence being in Sub-Saharan African countries (2,3). HIV type 1 is the most prevalent type of this virus (4).…”
Section: Introductionmentioning
confidence: 99%